Evolution of Vertebrate GnRH Receptors from the Perspective of a Basal Vertebrate - Sower, Stacia A.; Decatur, Wayne A.; Joseph, Nerine T.; Freamat, Mihael (Frontiers in Endocrinology, 2012)
This minireview provides the current status on gonadotropin-releasing hormone receptors (GnRH-R) in vertebrates, from the perspective of a basal vertebrate, the sea lamprey, and provides an evolutionary scheme based on the recent advance of whole genome sequencing. In addition, we provide a perspective on the functional divergence and evolution of the receptors. In this review we use the phylogenetic classification of vertebrate GnRH receptors that groups them into three clusters: type I (mammalian and non-mammalian), type II, and type III GnRH receptors. New findings show that the sea lamprey has two type III-like GnRH receptors and an ancestral type GnRH receptor that is more closely related to the type II-like receptors. These two novel GnRH receptors along with lGnRH-R-1 share similar structural features and amino acid motifs common to other known gnathostome type II/III receptors. Recent data analyses of the lamprey genome provide strong evidence that 2 whole rounds of genome duplication (2R) occurred prior to the gnathostome-agnathan split. Based on our current knowledge, it is proposed that lGnRH-R-1 evolved from an ancestor of the type II receptor following a vertebrate-shared genome duplication and that the two type III receptors resulted from a duplication within lamprey of a gene derived from a lineage shared by many vertebrates.